2022
DOI: 10.3389/fenrg.2022.766865
|View full text |Cite
|
Sign up to set email alerts
|

Fission Gas Behaviors and Relevant Phenomena in Different Nuclear Fuels: A Review of Models and Experiments

Abstract: Reactor structural integrity and nuclear safety are seriously affected by the fission gas behaviors and relevant physical phenomena in nuclear fuels. In this review, the fission gas behavior and relevant phenomena in different fuels for both models and experiments have been comprehensively overviewed, including fission gas release, gap/plenum pressure, grain growth, swelling, fission gas diffusion coefficients, and fuel cladding mechanical and chemical interactions under irradiations. The fission gas behaviors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 80 publications
(204 reference statements)
0
1
0
Order By: Relevance
“…1/3 (17) where Bu is the burnup. The above two asymptotic expressions can be integrated into a single expression due to the following two important remarks: First,…”
Section: The Incubation Thresholdmentioning
confidence: 99%
See 1 more Smart Citation
“…1/3 (17) where Bu is the burnup. The above two asymptotic expressions can be integrated into a single expression due to the following two important remarks: First,…”
Section: The Incubation Thresholdmentioning
confidence: 99%
“…As mentioned earlier, nuclear fuel performance is greatly affected by fission gas behavior. Moreover, fission gas behavior is related to the integrity and safety of nuclear power plants [17].…”
Section: Introductionmentioning
confidence: 99%
“…Many publications have shown that most of these bubbles are a group of non-reactive fission gases (xenon and krypton) emitted during the operation or shutdown of the reactor and are related to the level of burnup. Therefore, researchers have been interested in studying the growth of these gas bubbles resulting from fission within different types of nuclear fuel [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%